Call the Feds!

We¶ve Got Nested Radicals!
Alan Craig
F. Lane Hardy Seminar
11-3-08
What are Nested Radicals?
2 2 2 2
2 2 2
2 2

Examples:
We could keep this up
forever!
. + + + + + + 2 2 2 2 2 2
If we did,
what would we get?
. + + + + + + 2 2 2 2 2 2
= ?
Let¶s work up to it.
What are the values of these expressions?
? 2 2 2 2 2
? 2 2 2 2
? 2 2 2
? 2 2
? 2
<
<
<
<
<
Let¶s work up to it.
What are the values of these expressions?
? 2 2 2 2 2
? 2 2 2 2
? 2 2 2
? 2 2
1.414 2
<
<
<
<
<
What are the Values?
? 2 2 2 2 2
? 2 2 2 2
? 2 2 2
1.848 2 2
1.414 2
<
<
<
<
<
What are the Values?
? 2 2 2 2 2
? 2 2 2 2
1.962 2 2 2
1.848 2 2
1.414 2
<
<
<
<
<
What are the Values?
? 2 2 2 2 2
1.990 2 2 2 2
1.962 2 2 2
1.848 2 2
1.414 2
<
<
<
<
<
What are the Values?
1.998 2 2 2 2 2
1.990 2 2 2 2
1.962 2 2 2
1.848 2 2
1.414 2
<
<
<
<
<
What value is this sequence
of numbers approaching?
/
1.998
1.990
1.962
1.848
1.414
Now what do you think the value of
this infinite nested radical is?
? 2 2 2 2 2 2 = + + + + + + .
1.998 2 2 2 2 2
1.990 2 2 2 2
1.962 2 2 2
1.848 2 2
1.414 2
} + + + +
} + + +
} + +
} +
}
You¶re Right!
2 2 2 2 2 2 2 ! .
Let¶s see an example of where an
infinite nested radical could arise.
Warning: Brief Excursion into
Trigonometry!
Trigonometry
Half-Angle Formula
‡ We will use the half-angle formula for cosine
to take another look at this sequence and its
limit.
2
cos 1
2
cos
o o
s !
¹
º
¸
©
ª
¨
Let¶s use the formula to find .
so ,
2
2
4
cos Now,
2
4
cos 1
8
cos
=
¹
º
¸
©
ª
¨
¹
º
¸
©
ª
¨
+
=
¹
º
¸
©
ª
¨
T
T
T
¹
º
¸
©
ª
¨
8
cos
T
Let¶s use the formula to find .
2
2
2
1
2
4
cos 1
8
cos
+
=
¹
º
¸
©
ª
¨
+
=
¹
º
¸
©
ª
¨
T
T
¹
º
¸
©
ª
¨
8
cos
T
Let¶s rationalize the last expression by
multiplying numerator and denominator by 2.
Let¶s use the formula to find .
4
2 2

2 2
2
2
2
1

2
2
2
1
2
4
cos 1
8
cos

!
™
™
¹
¹
º
¸
©
©
ª
¨

!

!
¹
º
¸
©
ª
¨

!
¹
º
¸
©
ª
¨
¹
º
¸
©
ª
¨
8
cos
Let¶s use the formula to find .
2
2 2
4
2 2

2
2
2
1
2
4
cos 1
8
cos

!

!

!
¹
º
¸
©
ª
¨

!
¹
º
¸
©
ª
¨
¹
º
¸
©
ª
¨
8
cos
Let¶s use the formula to find .
2
2 2
4
2 2

2
2
2
1
2
4
cos 1
8
cos

!

!

!
¹
º
¸
©
ª
¨

!
¹
º
¸
©
ª
¨
¹
º
¸
©
ª
¨
8
cos
Now multiply both sides by 2.
Let¶s use the formula to find .
2 2
8
cos 2

2
2 2
4
2 2

2
2
2
1
2
4
cos 1
8
cos
!
¹
º
¸
©
ª
¨

!

!

!
¹
º
¸
©
ª
¨

!
¹
º
¸
©
ª
¨
¹
º
¸
©
ª
¨
8
cos
Repeatedly using the ½ angle formula:
¹
º
¸
©
ª
¨
= + + +
¹
º
¸
©
ª
¨
= + +
¹
º
¸
©
ª
¨
= +
32
cos 2 2 2 2 2
16
cos 2 2 2 2
8
cos 2 2 2
T
T
T
Repeatedly using the ½ angle formula:
¹
º
¸
©
ª
¨
= + + +
¹
º
¸
©
ª
¨
= + +
¹
º
¸
©
ª
¨
= +
32
cos 2 2 2 2 2
16
cos 2 2 2 2
8
cos 2 2 2
T
T
T
As the angle o gets
smaller and smaller
approaching 0, what
value is the cos(o)
approaching?
Repeatedly using the ½ angle formula:
¹
º
¸
©
ª
¨
= + + +
¹
º
¸
©
ª
¨
= + +
¹
º
¸
©
ª
¨
= +
32
cos 2 2 2 2 2
16
cos 2 2 2 2
8
cos 2 2 2
T
T
T
Recall cos(0) = 1, so
2 cos(o) is approaching 2
as o approaches 0.
Repeatedly using the ½ angle formula:
´ ) 2 1 2 0 cos 2 2 2 2 2
0 as 1 cos
! ™ ! !

p p
.
o o
That is,
That¶s all the trigonometry
for this session.
We have shown in two different ways
that the equation µought¶ to be true
2 2 2 2 2 2 2 ! .
To Recap:
Now let¶s µprove¶ it.
2 2 2 2 2 2 2 ! .
Set x equal to the expression.
. ! 2 2 2 2 2 2 x
Square both sides.
. ! 2 2 2 2 2 2
2
x
Subtract the original equation
from the squared equation.
.
.
!
!
2 2 2 2 2 2
2 2 2 2 2 2
2
x
x
2
2 2 2 2 2 2
2 2 2 2 2 2
2
2
=
+ + + + + + =
+ + + + + + =
x x
x
x
.
.
Subtract the original equation
from the squared equation.
Now solve the equation.
2
2
! x x
Solve the equation.
0 2
2
2
2
= ÷
=
x x
x x
Solve the equation.
0 ) 1 )( 2 (
0 2
2
2
2
= + ÷
= ÷
=
x x
x x
x x
Solve the equation.
2
0 ) 1 )( 2 (
0 2
2
2
2
!
!
!
!
x
x x
x x
x x
Why did we not use x = -1?
So
2 2 2 2 2 2 2 ! .
What about?
. 3 3 3 3 3 3
Does
. 3 3 3 3 3 3
= 3 ???
Using the same process as
before, we get
0 3 3
3 3 3 3 3 3
3 3 3 3 3 3
2 2
2
! !
!
!
x x x x
x
x
.
.
Recall the Quadratic Formula
a
ac b b
x c bx ax
2
4
0
2
2
±
= ÷ = + +
0 3
2
= x x
‡ We have
‡ So a = 1, b = -1, and c = -3 and
2
13 1
) 1 ( 2
) 3 )( 1 ( 4 ) 1 ( ) 1 (
2
±
= ÷
±
= ÷
x
x
So, No, we do not get 3
3 . 2 3 3 3 3 3 3
so , 3 . 2
2
13 1
0 3
2
} + + + + + +
} ÷
±
= ÷ =
.
x x x x
Let¶s ask a slightly
different question.
‡ Is there a positive integer a, such that if we
replace 3 under the nested radical with a, the
nested radical will equal 3?
Let¶s ask a slightly different question.
‡ That is, is there an a that makes the equation
below true?
? 3 ! . a a a a a a
Let¶s ask a slightly different question.
‡ That is, is there an a that makes the equation
below true?
‡ Yes! And we are going to find it.
? 3 = + + + + + + . a a a a a a
Subtract the original equation
from the squared equation.
a x x
a a a a a a x
a a a a a a x
=
+ + + + + + =
+ + + + + + =
2
2
.
.
Finding a
2
4 1 1
0
2
a
x a x x
+ +
= ÷ =
(Using the quadratic formula)
Finding a
We want x = 3, so
2
4 1 1 a
x
+ +
=
3
2
4 1 1
=
+ + a
Finding a
÷ = + + ÷ =
+ +
6 4 1 1 3
2
4 1 1
a
a
Finding a

25 4 1 5 4 1
6 4 1 1 3
2
4 1 1
÷ = + ÷ = +
÷ = + + ÷ =
+ +
a a
a
a
Finding a
6
25 4 1 5 4 1
6 4 1 1 3
2
4 1 1
=
÷ = + ÷ = +
÷ = + + ÷ =
+ +
a
a a
a
a
So we have shown that
3 6 6 6 6 6 6 ! .
Now let¶s generalize our result.
‡ µProve¶ that for any integer k > 1, there is a
unique positive integer a, such that
k a a a a a a = + + + + + + .
Note: The following is not a true mathematical proof of this theorem (which would
use limits of bounded, monotonically increasing sequences) but does suggest the
core reasoning and result of such a proof.
Finding a
1 2 4 1
2
4 1 1
! !

k a k
a
Finding a

1 4 4 4 1
1 2 4 1
2
4 1 1
2
!
! !

k k a
k a k
a
Finding a

1 4 4 4 1
1 2 4 1
2
4 1 1
2 2
! !
! !

k k a k k a
k a k
a
Finding a
) 1 (
1 4 4 4 1
1 2 4 1
2
4 1 1
2 2
!
! !
! !

k k a
k k a k k a
k a k
a
We have shown that
For any integer k > 1, there is exactly one integer
a = k (k - 1), such that
k a a a a a a = + + + + + + .
We have shown that
For any integer k > 1, there is exactly one integer
a = k (k - 1), such that
k a a a a a a = + + + + + + .
That is, every integer can be represented as an
infinite nested radical!
Example: k = 4
4 12 12 12 12 12 12 ! .
12 3 4 ) 1 ( = ™ = = k k a
5 20 20 20 20 20 20 ! .
20 4 5 ) 1 ( = ™ = = k k a
Example: k = 5
Alternatively, we might have noticed that
we need to solve
in such a way that we get two numbers
that multiply to make a and subtract to
make 1. Further, one of the numbers must
be k. (Why?) Thus, the other number
must be k - 1 and a must be k (k - 1).
Another Way
0
2
= a x x
That is
) 1 (
1
, 1 and
: other the and numbers the of one be Let
2
2
! !
! ! !
! ! ™
k k k k a
k a k
k
a
k
k
a
h
h k a h k
h k
The END?
The END?
No!
This is way too much fun!
Let¶s Kick it Up a Notch!
. + + + + + + a b a b a b a b a b a
. + + + + + + a b a b a b a b a b a
Note that what we did before
was a special case of this
expression with b = 1.
Let¶s Kick it Up a Notch!
k a b a b a b a b a b a ! .
For each integer k > 1, there are
exactly k - 1 pairs of integers a and
b, 0 < b < k, that satisfy this equation.
Further,
). ( b k k a !
Let¶s Kick it Up a Notch!
As before, square the equation.
.
.
!

!
a b a b a b a b a b a
b
a x
a b a b a b a b a b a x
2
2
But before we subtract the original equation
from the squared equation, we must isolate the
radical (so that it will subtract away).
Now subtract.
0
2
2
=

+ + + + + + =
+ + + + + + =

x
b
a x
a b a b a b a b a b a x
a b a b a b a b a b a
b
a x
.
.
Now subtract.
0 0
2
2
2
= ÷ =

+ + + + + + =
+ + + + + + =

a bx x x
b
a x
a b a b a b a b a b a x
a b a b a b a b a b a
b
a x
.
.
We will solve this by
factoring now but keep
it in mind for later.
For integer solutions of
we need two integers that multiply to
make a and have a difference of b.
One of the numbers must be k, so the
other is k - b. Thus,
Factor
0
2
! a bx x
) ( b k k a =
There are exactly k ± 1 such pairs
a and b:
(k ± 1) Pairs
1 1
2 2

3 ) 3 (
2 ) 2 (
1 ) 1 (
) (
™
™

=
k k
k k
k k
k k
k k
b b k k a
/ / /
(difference)
If k = 4, the k ± 1 = 3 pairs a and b
are:
Example: k = 4
3 4 1 4
2 8 2 4
1 12 3 4

! ™
! ™
! ™
b a
Example: k = 4
4 8 2 8 2 8 2 8 2 8 2 8 ! .
4 12 12 12 12 12 12 = + + + + + + .
4 4 3 4 3 4 3 4 3 4 3 4 = + + + + + + .
One Last Thought
. +
+
+
+
+
b
a
b
a
b
a
b
a
b
Consider this continued fraction:
.

!
b
a
b
a
b
a
b
a
b x
Suppose it converges to x, then
.

!
b
a
b
a
b
a
b
a
b x
Notice the shaded area is also x
Rewriting the continued fraction
x
a
b x
b
a
b
a
b
a
b
a
b x !

!
.
See what we get!
0
2
= ÷
+ = ÷
+
+
+
+
+ =
a bx x
x
a
b x
b
a
b
a
b
a
b
a
b x
.
Does this look familiar?
Yes, these are equal!!!
.
.
!

a b a b a b a b a
b
a
b
a
b
a
b
a
b
In particular, set a = b = 1.
??? 1 1 1 1 1 1 1 1 1
1
1
1
1
1
1
1
1
1
! !

.
.
The Golden Ratio J
2
5 1
1 1 1 1 1 1 1 1 1
1
1
1
1
1
1
1
1
1
+
= + + + + + =
+
+
+
+
+
.
.
(But that¶s another F. Lane Hardy talk.)
. End End End End End
?
Reference
Zimmerman, S., & Ho, C. (2008). On infinitely nested
radicals. Mathematics Magazine, 81(1), 3-15.

Sign up to vote on this title
UsefulNot useful